Cooperative / competitive factor analysis for optimal planning and management of a dynamic domain using simulation - Chong, Choon Jeng. (2009)
A system dynamics study was done on a real life PCBA product's internal supply chain to investigate the dynamic behavior within the chain. The study was done in two respects, in respect to the flow of information and the flow of materials within the chain. The dynamic behavior was explored and enhanced in detail, using a combination of system design, simulation, analysis and optimization techniques.